Competence Mining of Vancomycin (VAN) in the Management of Infections Due to Bacterial Strains With High VAN Minimum Inhibitory Concentrations (MICs): A Novel Dosing Strategy Based on Pharmacokinetic/Pharmacodynamic Modeling - Song, Xiangqing; Zeng, Meizi; Wu, Yi; Pan, Yong (Frontiers in Microbiology, 2021)
The increasing emergence of bacterial strains with high VAN MICs (BSH-VAN-M), such as Enterococcus faecalis, Enterococcus faecium, Staphylococcus aureus, Staphylococcus epidermidis and Streptococcus bovis, results in growing concern that VAN is not effective against these isolates. Due to the limited data on VAN against BSH-VAN-M and the application limits of drugs currently considered to be effective for BSH-VAN-M, exploration of “new usages for old drugs” is reasonable to improve and maximize the efficacy of existing antibiotics. This study aimed to construct a novel dosing strategy to mine the competence of VAN in the management of BSH-VAN-M infections. Herein, we optimized the traditional intermittent i.v. infusion (TIII) method to create an optimal two-step infusion (OTSI). With pharmacokinetic (PK)/pharmacodynamic (PD) modelling at the targeted ratio of the daily area under the concentration-time curve (AUC0-24) to the minimum inhibitory concentration (MIC) (AUC0-24/MIC) of 400, we used Monte Carlo simulations to evaluate the efficacy of 25 VAN regimens (including 15 OTSI regimens and 10 TIII regimens with daily doses of up to 6 g) to treat pneumonia, meningitis, sternal osteomyelitis, mastitis, pleuritis, bacteraemia and bacterial pericarditis resulting from isolates with MICs of ≤64 mg/L and to the current Enterococcus faecalis, Enterococcus faecium, Staphylococcus aureus, Staphylococcus epidermidis and Streptococcus bovis populations with a pooled MIC distribution. Our data indicated that 4 g/day VAN, with an OTSI but not a TIII, for mastitis, pleuritis, bacteraemia and bacterial pericarditis due to isolates with MICs of ≤4 mg/L or to the current Enterococcus faecalis, Staphylococcus aureus, Staphylococcus epidermidis and Streptococcus bovis populations achieved the desired PK/PD exposure at the AUC0-24/MIC target of 400. This study suggests the superiority and feasibility of OTSI relative to TIII for the competence mining of VAN against BSH-VAN-M from the perspective of PK/PD and provides a new resource for understanding how PK/PD modelling shapes the performance of VAN to meet the growing challenges of BSH-VAN-M infections.